2023
DOI: 10.25147/ijcsr.2017.001.1.102
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment Analysis of Students’ Experiences during Online Learning in a State University in the Philippines

Abstract: Purpose -This paper investigated the students' opinions during online learning. Performing sentiment analysis (SA) of students' experiences during online learning helps academic institutions and educators to understand their students, gauge their existing processes and delivery of instruction, and promote meaningful learning experiences from it. 1288Method -The study utilized the sentiment analysis approach in obtaining the polarity, subjectivity, and presentation of visualization results. The student-responde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…The students' online learning experiences during the pandemic had been revealed through a machine learning analysis. Different issues related to the Internet connection, technology resources, quality of instruction, motivation, engagement, and others were reported (Santiago et al, 2022). When students during online learning have adapted well to the e-learning resources, digital meeting platforms, online learning systems, and learning engagement as utilized by the teachers and the learners as claimed (Santiago et al, 2021), it is also significant to explore the thoughts of the learners towards the implementation of the limited face-toface learning.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The students' online learning experiences during the pandemic had been revealed through a machine learning analysis. Different issues related to the Internet connection, technology resources, quality of instruction, motivation, engagement, and others were reported (Santiago et al, 2022). When students during online learning have adapted well to the e-learning resources, digital meeting platforms, online learning systems, and learning engagement as utilized by the teachers and the learners as claimed (Santiago et al, 2021), it is also significant to explore the thoughts of the learners towards the implementation of the limited face-toface learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The lack of stable internet access can also make communication difficult. The absence of necessary technical and mental preparation and academic work overwhelms the learners (Santiago et al, 2022;Mailizar et al, 2020). Many students struggled and discovered that using technology to learn was distracting, so as long as it is safe to return to school, they would do so.…”
Section: Positive Thoughts or Feelings On The Implementation Of Limit...mentioning
confidence: 99%
“…Reaffirming what was indicated by Landínez and Rodríguez [31], they point out that it is possible to carry out sentiment analysis with different instruments to assess student satisfaction, which will lead to the fact that, based on the information obtained, it is possible to make decisions that guarantee an efficient allocation of resources to programs or faculties within educational institutions. Likewise, according to Ppachristopoulos et al [39], the development of applications of the sentiment analysis technique in the university environment will allow correcting the deficiency in the contextual understanding of student satisfaction; while Santiago et al [40] pointed out that the application of the analysis of feelings in the identification of learning experiences allows to extract more information regarding the critical thinking of the students. In addition, Kastrati et al [41] concluded that the analysis of feelings contributes to generating more effective feedback of the teaching process through the analysis of student opinions.…”
Section: Discussionmentioning
confidence: 99%
“…As of this writing, Fast Learners students remain one of the most underserved student populations in public school systems (80%); the challenge of not meeting their cognitive needs (60%) and their psycho-emotional needs (70%) remains true as teachers who work in public school education have to focus on their general education students who are still traversing the new normal. Teachers who are fortunate enough to have the presence of special education teachers may not be sufficient as these teachers focus on students with more severe special needs (80%) (Santiago et al, 2022). Specialized classrooms are often provided for Fast Learners.…”
Section: Fast Learners In Special Educationmentioning
confidence: 99%